A neuropsychological perspective on Attention-Deficit/Hyperactivity Disorder (ADHD): Consequences of a late diagnosis in children undergoing the literacy process (Research, Society and Development, 2025)
This study aims to investigate the neuropsychological view of Attention Deficit Hyperactivity Disorder (ADHD) and the consequences of late diagnosis in children undergoing literacy. The methodology adopted was qualitative research, of a bibliographic nature, through the collection and analysis of data extracted from materials published by authors and researchers in the field. The study seeks to present aspects related to brain and school development, environmental and genetic causes, affected brain areas, associated comorbidities, as well as the diagnostic and assessment process of the disorder. In addition, it addresses pharmacological treatment and discusses how the absence of qualified professionals contributes to late diagnosis, finally providing guidance for parents, caregivers, and educators.